2021
DOI: 10.1002/ajb2.1740
|View full text |Cite
|
Sign up to set email alerts
|

Limited evidence that larger acorns bufferQuercus rubraseedlings from density‐dependent biotic stressors

Abstract: Plant performance and functional traits vary considerably within species, particularly in response to environmental variation. Plant responses may reflect lifehistory trade-offs, such as between resource acquisition and resource conservation. Larger seeds may buffer young plants from the negative effects of environmental variation, such as limitations in nutrients or water. However, whether seed size plays a similar role in how plants respond to variation in their biotic environment, including competition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…However, Long and Jones ( 1996 ) and Clark and Schlarbaum ( 2018 ) revealed that neither acorn size nor mass could be used reliably as morphological indicators of seedling quality or to predict the survival of oak seedlings. Larger seeds deliver more resources at the early stages of seedling development but they do not necessarily buffer young plants from the negative effects of environmental variation (e.g., from limitations in nutrients or water) or competition of other plants (Jevon et al., 2021 ). However, larger acorns are attractive to seed consumers, so they can be more threatened by acorn predators (Buckley et al., 2006 ; Crawley, 2000 ; Merceron et al., 2017 ; Mezquida et al., 2021 ; Myczko et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, Long and Jones ( 1996 ) and Clark and Schlarbaum ( 2018 ) revealed that neither acorn size nor mass could be used reliably as morphological indicators of seedling quality or to predict the survival of oak seedlings. Larger seeds deliver more resources at the early stages of seedling development but they do not necessarily buffer young plants from the negative effects of environmental variation (e.g., from limitations in nutrients or water) or competition of other plants (Jevon et al., 2021 ). However, larger acorns are attractive to seed consumers, so they can be more threatened by acorn predators (Buckley et al., 2006 ; Crawley, 2000 ; Merceron et al., 2017 ; Mezquida et al., 2021 ; Myczko et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of Quercus and its economic importance in the eastern United States continued well into the early 20th century, when forest researchers began to notice and document the conversion of Quercus forests to different tree species (Abrams andDowns 1990, Hix andLorimer 1991). The recognition of a potential future decline in the abundance of Quercus triggered a flurry of research focused on seedling and sapling germination and regeneration (Gilbert et al 2003, Dey et al 2008, Hart and Kupfer 2011, Jevon et al 2021. As researchers work to untangle the complexities of Quercus-dominated forests, there has not always been agreement among scientists about how to interpret the data sets we have developed; however, there has always been agreement that researching these ecosystems has high scientific and forest conservation value.…”
mentioning
confidence: 99%